1937
DOI: 10.1002/cber.19370700322
|View full text |Cite
|
Sign up to set email alerts
|

Fichtenlignin (XVI. Mitteil. über Lignin)

Abstract: Das Prinzip der Veratherung ist iiberlagert von einem sekundaren Kondensationsvorgang, der sich vielleicht zum Teil schon physiologisch in der lebenden Zelle, weiterhin postmortal in der Pflanze und bei der chemischen Behandlung wahrend der Isolierung vollzieht. Hierbei bilden sich Renzopyran-oder Benzofuran-Systerne.Die bisherigen Beobachtungen haben sich diesem Schema einfdgen lassen. Auch den Ergebnissen dieser Untersuchung halt es stand, und es scheint uns miiglich, durch eine in1 Rahmen der obigen Ausfiih… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
4
0

Year Published

1937
1937
1939
1939

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…Klason {17), for example, made the suggestion that an ethylene oxide ring is opened with addition of the sulfurous acid so as to form a sulfonic acid and a hydroxyl group. Freudenberg (8) supports the theory of the opening of an oxygen ring by model experiments with socalled Erdtman's acid, which is obtained on oxidation of dehydrodiisoeugenol.…”
supporting
confidence: 54%
See 1 more Smart Citation
“…Klason {17), for example, made the suggestion that an ethylene oxide ring is opened with addition of the sulfurous acid so as to form a sulfonic acid and a hydroxyl group. Freudenberg (8) supports the theory of the opening of an oxygen ring by model experiments with socalled Erdtman's acid, which is obtained on oxidation of dehydrodiisoeugenol.…”
supporting
confidence: 54%
“…Hágglund and Carlsson {12), on the other hand, found that in the formation of ligninsulfonic acid a new hydroxyl group is formed for each sulfonic group entering the lignin, which led them to conclude that the sulfurous acid opens an oxygen bridge. After taking these results under consideration and finding that this new hydroxyl group is phenolic in character, Freudenberg (8) postulated that the sulfonation may occur in two steps, which may or may not be mutually dependent. In the first stage a ring system is opened with formation of a phenolic and of a secondary hydroxyl group; in the second stage the latter is substituted by a sulfonic group, either directly or after previous splitting off of water.…”
mentioning
confidence: 99%
“…The -SOsH groups in formulae like XXXI and XXXII are to be replaced by -SCH2 ' COOH. The evidence for this conception is found in the results of methylation and oxidation by means of which small yields of veratric and isohemipinic acids are obtained(84). Furthermore, exp eriments on substances known to contain such linkages support this conception (ct. pp.…”
mentioning
confidence: 78%
“…Alkali.-Spruce lignin (67,84), or better the wood itself, subse quent to methylation with diazomethane, 90 minutes cooking with 70 per cent potassium hydroxide at 165 to 1700, methylation with dimethylsulphate, and oxidation with permanganate yields (calculated from lignin content) : 20 to 21 per cent veratric acid (XXIV), 6 to 12 per cent isohemipinic acid (XXV), 2 to 3 per cent dehydrodiveratric acid (XXVI), and traces of trimethylgallic acid.…”
Section: Degradation Following Cleavage Of Ether Bondsmentioning
confidence: 99%
See 1 more Smart Citation